MEMBANGUN APLIKASI SMS GATEWAY DENGAN MENGGUNAKAN APLIKASI ANDROID SMS GATEWAY DI UNIVERSITAS BANTEN JAYA - Waliadi Gunawan; Ely Nuryani; Joko Wahyu Utomo (LPPM Unbaja, 2020)
Education institutions, especially universities, can not be separated from the activities that will surely related to academic information. Announcements made automatically by the system in one direction. When the internal information is collected, then the system will do the writing into database that is then processed to be sent to the corresponding number. So the message or information can be delivered quickly. A system used to simultaneously send SMS / Broadcast one them is the SMS Gateway. For now Academic School of Computer Science have yet to implement SMS Gateway application, and for that reason the authors decided to design and build a SMS Gateway Application that will be used as a tool that can help in the management of the notification to immediately. Of these problem led to the idea create web application SMS Gateway, SMS Gateway, and Android Application, which also can perform data management and messaging. The methodology used in the making of appliction is the waterfall methods. Web programming language is php. While android application using java. To view using Jquery, CSS, and Boostrap. MySql for Database. Tool and Editions used is XAMPP for windows 1.7.3, Photoshop, and Android Studio